PENGARUH RELIGIUSITAS TERHADAP ETIKA BERBISNIS (Studi pada RM. Padang di Kota Malang) - ., Fauzan (Jurnal Manajemen dan Kewirausahaan, 2013)
The purpose of this research was to examine the influence of religiousity to ethics of business in the RM. Padang in Malang. This type of research was the survey. The population was the owners of RM. Pa-dang in Malang and the sampling technique was simple random sampling. This research used multiple re-gression linear method. The result indicated that simultaneously all independent variables had a positive and significant effect to dependent variable. Partially, ritual/syari’ah and consequential/akhlaq dimension had a positive and significant effect to ethics of business. Ideology and Intelectual dimension did not have a positive and significant effect to ethic of business. The most dominant dimensions of religiousity that influenced busi-ness ethics was the consequential/akhlaq.